AHL-based QS signalling promotes uropathogenic Escherichia coli settlement through the de-repression of biofilm formation by SdiA - Celia Mayer; Fadi Soukarieh; Manuel Simões; Saskia-Camille Flament-Simon; Miguel Cámara; Manuel Romero (PLoS ONE, 2025)
Uropathogenic Escherichia coli (UPEC) are among the first pathogens to colonise in catheter and non-catheter-associated urinary tract infections. However, these infections are often polymicrobial, resulting in multi-species infections that persist by forming biofilms. Living within these highly antimicrobial tolerant communities, bacteria can establish intra- and inter-specific interactions, including quorum sensing (QS)-mediated signalling mechanisms, which play a key role in biofilm establishment and maturation. Although E. coli does not produce N-acylhomoserine lactones (AHLs), it possesses an orphan LuxR-type receptor, SdiA, which can bind these QS signals released by other Gram-negative bacteria, modulating several virulence-associated phenotypes including biofilm formation. Despite biofilms being considered a major public health challenge due to their persistence and resilience, the knowledge of the SdiA role in biofilm regulation and UPEC fitness in mixed biofilms is limited compared to enteropathogenic E. coli. We have used a ΔsdiA mutant and phenotypic analysis to investigate the SdiA influence on UPEC single and mixed biofilms with Pseudomonas aeruginosa. SdiA was found to inhibit UPEC biofilm and addition of AHLs enhanced E. coli surface colonisation via SdiA-mediated de-repression of biofilm. We also confirmed the low specificity of SdiA for AHLs, demonstrating the SdiA importance in tightly regulating the UPEC free-living and biofilm-associated lifestyles.